A Lysosomal Concept of the Platelet Release Reaction and Viscous Metamorphosis - Kowalski, E; Kopeć, Maria; Węgrzynowicz, Z; Hurwic, Maria; Budzyński, A. Z (Thrombosis and Haemostasis, 1966)
A hypothesis is put forward according to which the platelet release reaction and viscous metamorphosis are connected with platelet lysosome activation. An essential element of this hypothesis is the assumption of ATPase activation which results in ATP breakdown and ADP release.The following findings are described :1. A variety of agents was studied in regard to their ability to induce the release reaction. It was found that thrombin, trypsin, papaine, elastase, protease from streptomyces griseus, connective tissue “extracts”, contact factor preparations, kaolin suspensions and Triton X-100 induce the release of adenine nucleotides from platelets.2. All the studied release inducing agents activated to some extend the platelet acid phosphatase.3. Streptolysine 0 and staphylocoagulase induce the platelet release reaction as well as the activation of platelet acid phosphatase.4. Agents known to labilize liver lysosomes induce some release of adenine nucleotides from platelets and activate platelet acid phosphatase.5. Prednisolone succinate which is known to stabilize lysosomes, inhibits the activation of acid phosphatase provoked by release inducing agents.6. The activation of liver lysosome acid phosphatase by platelet release inducing agents was irregular and small.7. The ATPase activity of thrombosthenin preparations and of dialysed platelets was found to be increased by thrombin.8. N-ethylmaleimid inhibits the platelet release reaction while ouabaine did not so.The proposed hypothesis is discussed in the light of the recent lysosome research.